2022
DOI: 10.1029/2021gl097051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrate on the Photochemical Production of Carbonyl Sulfide From Surface Seawater

Abstract: Carbonyl sulfide (COS) plays an important role in the sulfur cycle and climate change. Yet, much remains unknown about the photochemical mechanisms of COS in nutrient‐rich seawater. We measured the photochemical production rates of COS in the surface seawater of the Indian Ocean under sunlight irradiation. The photochemical production of COS was mainly initiated by ultraviolet (UV) radiation with UVA contributing approximately 68% to the total COS production. Using cysteine, a typical proxy of dissolved organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…More than 80% of photoproduction of both the OCS and CS 2 was driven by UV radiation. Similar wavelength dependence of OCS photoproduction was also reported by Li et al through laboratory culture . This phenomenon may be due to the photosensitizers having wavelength-selective absorption and mainly absorbing UV radiation.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…More than 80% of photoproduction of both the OCS and CS 2 was driven by UV radiation. Similar wavelength dependence of OCS photoproduction was also reported by Li et al through laboratory culture . This phenomenon may be due to the photosensitizers having wavelength-selective absorption and mainly absorbing UV radiation.…”
Section: Resultssupporting
confidence: 89%
“…After normalizing by photon flux density, OCS and CS 2 photoproduction rates in the KOE significantly exceeded those in the NPSG (Table S5), which indicated abundant photosensitizers and/or precursors in the KOE. Figures S3 and c demonstrated that KOE upwelling likely influenced the availability of dissolved organic matter and nitrate for solar radiation exposure, enriching surface photochemical processes with photosensitizers and precursors. , Additionally, upwelling-associated nutrient influx boosted surface phytoplankton growth, furthering in situ organic matter production. Lennartz et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations